Estratigrafia de sequências do intervalo aptiano ao albiano na Bacia do Araripe, NE do Brasil - Rojas, Fabio Enrique Malagon (2009)
This study has as a main objective to make a detailed stratigraphic analysis of the Aptian-Albian interval in the east part of Araripe Basin, NE of Brazil which correspond, litostratigraphically, to Rio Da Batateira, Crato, Ipubi and Romualdo formations. The stratigraphic analysis was based on three different stages, the 1D, 2D and 3D analysis; these ones were adapted to the sequence stratigraphy concepts in order to create a chronostratigraphic framework for the study area within the basin. The database used in the present study contains field and well information, wells that belong to Santana Project, carried out by the Ministério de Minas e Energia- DNPM- CPRM from 1977 to 1978. The analysis 1D, which was done separately for each well and outcrop allowed the recognition of 13 sedimentary facies, mainly divided based on predominant litologies and sedimentary structures. Such facies are lithologically represented by pebble, sandstones, claystones, margas and evaporates; these facies are associated in order to characterize different depositional systems, that integrate from the continental environment (fluvial system and lacustre), paralic system (delta system and lagunar) to the marine environment (shelfenvironment). The first one, the fluvial system was divided into two subtypes: meandering fluvial system, characterized by fill channel and floodplain deposits; the facies of this system are associated vertically according to the textural thinning upward cycles (dirting-up trend pattern in well logs). Lacustrine environment is mainly related with the lithotypes of the Crato Formation, it shows a good distribution within the basin, been composed by green claystone deposits and calcareous laminated. Deltaic System represented by prodelta and delta front deposits which coarsening upward tendency. Lagunar system is characterised by the presence of anhydrite and gypsum deposits besides the black claystone deposits with vegetal fragments which do not contain a fauna typically marine. The marine platform system is composed by successions of black and gray claystone with fossiliferous fauna of Dinoflagellates (Spiniferites Mantell, Subtilisphaera Jain e Subtilisphaera Millipied genre) typical of this kind of depositional system. The sedimentary facies described are vertically arranged in cycles with progradational patterns which form textural coersening upward cycles and retrogradational, represented by textural thinning dowward cycles. Based in these cycles, in their stack pattern and the vertical change between these patterns, the systems tracks and the depositional sequences were recognized. The Low System Track (LST) and High System Track (HST) are composed by cycles with progradational stack pattern, whereas the Trangessive System Track (TST) is composed by retrogradational stack pattern cycles. The 2D stratigraphic analysis was done through the carrying out of two stratigraphic sections. For the selection of the datum the deepest maximum flooding surface was chosen, inside the Sequence 1, the execution of these sections allowed to understand the behaviour of six depositional systems along the study area, which were interpreted as cycles of second order or supercycles (cycles between 3 and 10 Ma), according to the Vail, et al (1977) classification. The Sequence 1, the oldest of the six identified is composed by the low, transgressive and high systems tracks. The first two system tracks are formed exclusively by fluvial deposits of the Rio da Batateira Formation whereas the third one includes deltaic and lacustrine deposits of the Crato Formation. The sequences 2 and 3 are formed by the transgressive systems tracks (lake spreading phase) and the highstand system track (lake backward phase). The TST of these sequences are formed by lacustrine deposits whereas HST contains deltaic deposits, indicating high rates of sedimentary supply at the time of it s deposition. The sequence 4 is composed by LST, TST and HST, The TST4 shows a significant fall of the lake base level, this track was developed in conditions of low relation between the creation rate of space of accommodation and the sedimentary influx. The TST4 marks the third phase of expansion of the lacustrine system in the section after the basin´s rift, the lacustrine system established in the previous track starts a backward phase in conditions that the sedimentary supply rate exceeds the creation rate of space accommodation. The sequence 5 was developed in two different phases, the first one is related with the latest expansion stage of the lake, (TST5), the basal track of this sequence. In this phase the base level of the lake rose considerably. The second phase (related to the TST5) indicates the end of the lacustrine domain in the Araripe Basin and the change to lagunar system ant tidal flat, with great portions in the supratidal. These systems were formed by restricted lagoons, with shallow level of water and with intermittent connections with the sea. This, was the phase when the Araripe Basin recorded the most several arid conditions of the whole interval studied, Aptian Albian, conditions that allow the formation of evaporitic deposits. The sequence 6 began its deposition after a significant fall of the sea (LST6). The sequence 6 is without any doubtlessly, the sequence that has deposits that prove the effective entrance of the sea into the Araripe Basin. The TST6, end of this sequence, represents the moment which the sea reaches its maximum level during the Aptian Albian time. The stratigraphic analysis of the Aptian Albian interval made possible the understanding that the main control in the development of the depositional sequences recognized in the Araripe Basin were the variations of the local base level, which are controlled itself by the climate changes